(untitled) (Raparin Journal of Humanities (RJH), 2023)
This research aims to conduct a relevance-theoretic analysis of an interview with American President Joe Biden on ABC’s late-night talk show. Relevance Theory was developed by Sperber and Wilson (1986/1995) as an inference-based framework for understanding the cognitive interpretation of language. The model posits that in any given circumstance, the recipient must consider what others say relevant. The recipient must consider what others say is as relevant in any given circumstance. The descriptive-qualitative approach was used to illustrate how Biden constructs his sentences to provide the listener with sufficient evidence to grasp his intended meaning and how the listener employs comprehension strategies to understand the speaker’s underlying meaning. Therefore, the research first reveals that Biden conveys his communicative goals clearly and gives enough supporting evidence for the receiver to deduce some of his intentions. Second, for effective communication, both parties must share cognitive context.